News Shocks under Financial Frictions - Christoph Görtz; John D. Tsoukalas; Francesco Zanetti (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We examine the dynamic effects and empirical role of TFP news shocks in the context of frictions in financial markets. We document two new facts using VAR methods. First, a (positive) shock to future TFP generates a significant decline in various credit spread indicators considered in the macro-finance literature. The decline in the credit spread indicators is associated with a robust improvement in credit supply indicators, along with a broad based expansion in economic activity. Second, VAR methods also establish a tight link between TFP news shocks and shocks that explain the majority of un-forecastable movements in credit spread indicators. These two facts provide robust evidence on the importance of movements in credit spreads for the propagation of news shocks. A DSGE model enriched with a financial sector generates very similar quantitative dynamics and shows that strong linkages between leveraged equity and excess premiums, which vary inversely with balance sheet conditions, are critical for the amplification of TFP news shocks. The consistent assessment from both methodologies provides support for the traditional `news view' of aggregate fluctuations.
Keywords: E20; E30; 330; news shocks; business cycles; DSGE; VAR; Bayesian estimation